Pengaruh Hasil Investasi, Ukuran Perusahaan, dan Hasil Underwriting terhadap Laba Perusahaan Asuransi Syariah - Endi Septika, Anggie Eka; Mariana, Mariana (Jurnal Profiet, 2024)
This research aims to analyze the influence of investment returns, company size, and underwriting results on profits in sharia insurance companies in Indonesia for the period 2018 - 2022. This research uses a quantitative approach with secondary data analysis taken from the annual financial reports of sharia insurance companies registered in Financial Services Authority (OJK). The analytical method used is multiple linear regression to test the influence of independent variables on sharia insurance company profits as the dependent variable. The research results show that investment returns and company size have an influence on the profits of sharia insurance companies, while underwriting results do not show any influence on profits of sharia insurance companies in the period studied. Keywords: Company Profit, Investment Results, Company Size, Underwriting Results, Sharia Insurance.